Implementasi Partisipatif Natural dalam Evaluasi Program Pendidikan di SDIT At-Taqwa - Salma, Masyqi; Merduani, Frestinata Arum; Sya’diyah, Khalimatus; Amalia, Kaniati (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
The type of research used in this writing is descriptive qualitative research. Descriptive qualitative is an analytical technique focused on understanding a problem, context, complexity, and subjectivity. Qualitative data sources can be text, audio, and visual data. The subject in this research is the vice principal for curriculum. While the data collection techniques in this study we used 2 ways, namely by conducting in-depth interviews and literature studies. This research uses primary data. The purpose of this study is that the evaluation of educational programs at SDIT AT TAQWA can provide an in-depth understanding of the quality of education provided, in line with the school's vision and mission. The results of this evaluation can be used as a basis for identifying the strengths and weaknesses of the education program, as well as formulating corrective actions that can increase the effectiveness and suitability of the program with the desired educational objectives.